Peran Media Sosial Instagram dan Tiktok dalam Upaya UMKM Meningkatkan Pemasaran Batik Besurek di Kota Bengkulu - Yuni Yulita; Susiyanto Susiyanto; Lesti Heriyanti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the use of social media by Santi Batik MSME in promoting Batik Besurek, a traditional cultural product of Bengkulu. In the digital era, platforms such as Instagram and TikTok play a significant role in building brand identity and expanding marketing reach. The research adopts a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that although Santi Batik actively uses social media, the management of its accounts remains unstructured due to limited time, digital skills, and the absence of a dedicated social media administrator. Instagram is mainly used to showcase product images, while TikTok is utilized to display live production processes. However, the lack of consistent content planning limits the effectiveness of promotional efforts. Through the lens of Symbolic Interactionism, the study identifies that social media not only serves as a marketing tool but also as a symbolic space where cultural meanings are constructed and emotional bonds between business owners and consumers are formed. In conclusion, social media holds great potential in supporting the presence of local cultural products such as Batik Besurek, yet it requires enhanced digital capabilities and more strategic content planning to ensure consistent and impactful promotion in the face of an increasingly competitive digital market.